The Basis for the Implication of Powers of International Organizations - Gadkowski, Andrzej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The aim of this article is to present the basis of the implication of powers of international organizations. This topic is not only of great interest and import from the point of view of the theory of international organizaizations, but also from that of the practice of international organizations, particularly important institutions of international cooperation. The author discusses the nature of the basis for such implication before then examining the implication of powers within the context of international organizations’ expressly granted powers.